Development of The Nearest Tourism Determination Application using Dijkstra Algorithm - Edi Iskandar; Edy Prayitno; Deborah Kurniawati; Al Amin Ali Imron (AIBPM Publisher, 2019)
By applying information and communication technology, an application can be developed that can help tourists determine the fastest route to reach tourist destinations, to avoid wasting time on trips. This study aims to create a prototype mobile application that can help tourists determine the path with the shortest route to tourist attractions. The research was carried out by using the Dijkstra algorithm and web service to access the tourism database in Bantul Regency, Yogyakarta Special Region as a case study. The fastest route generated by this application is compared to the route suggested by Google Map with a result of 7.24 km and 7.4 km. From the results of these comparisons it can be concluded that the application can determine the closest route from the various alternatives available.